Solve for n 5(3n+1)=2(5n-4)+6n

Math
5(3n+1)=2(5n-4)+6n
Since n is on the right side of the equation, switch the sides so it is on the left side of the equation.
2(5n-4)+6n=5(3n+1)
Simplify 2(5n-4)+6n.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
2(5n)+2⋅-4+6n=5(3n+1)
Multiply 5 by 2.
10n+2⋅-4+6n=5(3n+1)
Multiply 2 by -4.
10n-8+6n=5(3n+1)
10n-8+6n=5(3n+1)
Add 10n and 6n.
16n-8=5(3n+1)
16n-8=5(3n+1)
Simplify 5(3n+1).
Tap for more steps…
Apply the distributive property.
16n-8=5(3n)+5⋅1
Multiply.
Tap for more steps…
Multiply 3 by 5.
16n-8=15n+5⋅1
Multiply 5 by 1.
16n-8=15n+5
16n-8=15n+5
16n-8=15n+5
Move all terms containing n to the left side of the equation.
Tap for more steps…
Subtract 15n from both sides of the equation.
16n-8-15n=5
Subtract 15n from 16n.
n-8=5
n-8=5
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Add 8 to both sides of the equation.
n=5+8
Add 5 and 8.
n=13
n=13
Solve for n 5(3n+1)=2(5n-4)+6n

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top